Optimizing students’ narrative writing skill through story frame strategy at SMA Negeri 1 Loceret - Miftakhul Nur Aisah; Sujono Sujono; Triana Wuri Cahyanti (STKIP PGRI Nganjuk, 2025)
This research aimed to examine students' writing skills in narrative texts before using the Story Frame Strategy, to identify students' writing skills in narrative text after using the Story Frame Strategy, to determine whether there was a significant difference in students' achievement in writing narrative text before and after. This research employed a quantitative approach with a one-group pre-test and post-test design. The research was conducted at SMAN 1 Loceret in the academic year 2024/2025, with a sample of the study consisting of 34 students of class X-1, selected through purposive sampling. Data were analyzed using the Paired Sample t-Test with SPSS 27. The findings revealed that students’ narrative writing skills before the implementation of the Story Frame Strategy were relatively low, with a pre-test mean score of 64. After being taught using the Story Frame Strategy, their performance improved significantly, with the post-test mean score reaching 81.4. The alternative hypothesis (Hₐ) was accepted if the result of applying the Story Frame Strategy showed a significant effect on students' writing outcomes. The null hypothesis (H₀) was accepted if the result did not show a significant effect. This result indicated that H₀ was rejected and Hₐ was accepted. Therefore, it can be concluded that the Story Frame Strategy had a significant effect on improving tenth-grade students’ narrative writing skills at SMAN 1 Loceret.